Trust and Social Capital of Patients in Engkong Traditional Medicine in Binjai City - Riris Indriani, Riris (Talenta Publisher, 2023)
Health is the most important indicator for every human, when a person is declared healthy, all his activities will run well. If you look at health services in Indonesia, it shows there is a combination of modern medicine and traditional medicine. This research was conducted to interpret how social capital as a traditional treatment strategy engkong with the actions of people who choose decisions in curing diseases. On the other hand, it is also to describe that there is no coercion of a person to practice traditional medicine. The method used descriptive qualitative approach. Data collection techniques are carried out by observation, in-depth interviews and relevant literature studies. The results of the study can beÂ concluded the contribution of trust and social capital to patients is useful in traditional medicine and can also maintain the existence of traditional medicine. With the social capital in traditional engkong medicine in Binjai City, it will make it very easier for the surrounding community to carry out traditional healing, with the therapeutic kusuk technique carried out by Engkong doesnâ€™t produce side effects in the future. The most powerful social capital influence is the existence of networks and beliefs while those with weak influences are social values and norms.